Synthese kapazitätsoptimierter Antennensysteme mit messtechnischer Verifikation - Mahler, Tobias (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2018)
This work describes an optimization concept for mobile antenna systems. The so-called antenna synthesis determines optimal fixed antenna radiation patterns with the help of simulated or measured transmission channels. These radiation patterns increase the spectral efficiency and the reliability of the antenna system compared to conventional antennas with omnidirectional radiation patterns. Therefor the antenna systems are matched as best as possible to the predominant directions of the channel.